The secretome of the working human skeletal muscle—A promising opportunity to combat the metabolic disaster?. Issue 1 (February 2014) - Weigert, Cora; Lehmann, Rainer; Hartwig, Sonja; Lehr, Stefan; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> Recent years have provided clear evidence for the skeletal muscle as an endocrine organ. Muscle contraction during physical activity has emerged as an important activator of the release of the proteins and peptides called "myokines." Diverse proteomic profiling approaches were applied to rodent and human skeletal muscle cells to characterize the complete secretome, to study the regulation of the secretome during cell differentiation or the release of myokines upon contractile activity of myotubes. Several of the exercise‐regulated factors have the potency to mediate an interorgan crosstalk. The paracrine function of the secreted peptides and proteins to regulate muscle regeneration, tissue remodeling, and trainability can have direct effects on whole‐body glucose disposal and oxygen consumption. The overall composition and dynamic of the myokinome are still incompletely characterized. Recent advantages in metabolomics and lipidomics will add metabolites and lipids with autocrine, paracrine, or endocrine function to the contraction‐induced secretome of the skeletal muscle. The identification of these metabolites will lead to a more comprehensive view described by a new myo(metabo)kinome consisting of peptides, proteins, and metabolites.